P‐8.3: A Novel Wireless Transmission System for UHD Digital Art Display. (4th October 2019) - Guan, Enhui; WANG, Zhimao; Cheng, Xinyi; Zhang, Xiao; Li, Xianzhen; Chen, Shuo
Abstract : With the development of ultra‐high definition (UHD) display technology, the display system can make the picture more appealing and realistic. It is very difficult for us ordinary people to enjoy the traditional famous art works because of its expensive price and the rare amount. Compared with the traditional art works, the price of the novel UHD digital art display system is reasonable. What's more, it can provide the real sense as the realistic paintings. Besides the photo display, the customer also want the system display the UHD video. This paper presents a novel wireless transmission system based on the rk3399 chip from Rockchip with Wi‐Fi module, bluetooth module, ethernet network module and highspeed interface circuit for UHD digital art display, especially for UHD vedio. It is designed that a hardware system with smaller printed circuit board (PCB), lower power loss and lower price. Furthermore, the transmission rate is less than 300ms, which can provide an excellent watch enjoyment.